Can anticytokine therapy prevent unfavourable course of ulcerative colitis? - A. Yu. Baranovsky; E. A. Kondrashina; A. G. Kharitonov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To study potential of tumor necrosis factor-alpha inhibitor Remicade to prevent complications and unfavorable course of ulcerative colitis.Material and methods. Therapeutic role of Remicade was investigated in one of three compared groups (24 patients) with unfavourable prognosis (frequent relapses, continuous course, steroid-dependency, steroid resistance) and risk of complications.Results. Early onset of anticytokine therapy by Remicade has allowed to decrease frequency of unfavourable course from 83,3% (comparison group) and 78,3% (control group) to 12,5% and to prevent complications. Data of investigation prove, that so-called «top down» therapy with application of Remicade improves quality of life scores of patients in comparison to placebo (in 1 year) for over 18%, for 25,4% (in 2 years) and for 27,8% (in 3 years). Beneficial effect of anticytokine therapy in ulcerative colitis patients was revealed by parameters of general health, viability, mental health and social functioning.Conclusions. In cases of the prognosis of complications and unfavourable course of disease Remicade treatment should be started in maximally early terms.